(3fXQI eSJbHdjI Mhd EYOGO GdeYdejf aj GdYGde GdYQHjs - (3OhGfj, ceGds ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2009)
(3JJchf gPg GdhQbI GdHMKjI ef LRFjf QFjSjf(B: (3jJVef GdLRA GdChd eRGjG GdeYde GdegfjI GdJj JeqjRg Yf GdCTNGU GdYGOjjf, hOhQg Gdege GdPj jdYHg aj JMOjO eSJhi JQHjI GdeLJeY hJbOeg(B. (3ceG jJVef hUakG dhGbY EYOGO GdeYdejf hddeTcdGJ GdLhgQjI GdJj jYGfj efgG ef MjK feWjI gPG GdEYOGO hHQGeLg GdJbdjOjI aj eMJhGgG hWQGFb JOQjSgG hSjGSGJ GdbHhd ajgG(B. (3ceG jJYQV Edi GdeDJeQGJ hGdMdbGJ hGddLGf GdYQHjI GdJj JYbO HTCf EYOGO GdeYdejf, hGdWGHY GdQSej hGdYehej GdPj jShOgG hjSqjS eNQLGJgG(B. (3CeG GdLRA GdKGfj ajJfGhd GdJMOjGJ GdeSJbHdjI dEYOGO GdeYdejf aj GdYGde GdYQHj, hCgejI GdJacjQ GdJCedj dgPG GdEYOGO hVQhQI GSJNOGe GdfgL GdYdej ajg(B. (3Ke jfGbT GdJMOj GdcHjQ GdPj jhGLg GdbGOI GdJQHhjjf GdYQH aj JhajQ GdefGN GdefGSH ddeYdejf aj aJQI GdEYOGO djchfhG eTGQcjf aj YedjI GdJZjjQ HMjK jUHM GdeYde HYO aJQI GdEYOGO YfUQkG ddJZjjQ HOdkG ef Cf jchf YfUQkG jLH JZjjQg, EVGaI Edi CgejI GdJQcjR Ydi bjeI GdPGJ dOjg hYOe beY gPg GdPGJjI ef NdGd GdeZGdGI HGdehVhYjI(B. (3ceG jbOe gPG GdLRA HYV GdGJLGgGJ GdMOjKI aj EYOGO GdeYdejf eY GSJYQGV HYV GdfeGPL GdMOjKI aj Ohd CNQi(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Arab World; Educational prospective; Monde Arabe; Prospective; (3GdGSJTQGas; (3YGde YQHjs